Optimalization of the Nagari Owned Enterprise Program (BUMNag) Mitra Mandiri in Developing the Potential of Nagari Sungai Pua Agam Regency - Nadya; Rizki Syafril (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
Badan Usaha Milik Nagari Mitra Mandiri Sungai Pua is a business entity established in order to utilize the wealth of Nagari Sungai Pua which has the potential to be developed. Through its program, BUMNag is expected to be maximized in operating it and will be able to benefit the people of Nagari Sungai Pua. This study aims to determine the optimization of the Sungai Pua Nagari